Osprey, Pandion haliaetus, Depredates Common Eider, Somateria mollissima, Duckling - Blinn, Brenda M.; Violette, Vicky; Diamond, Antony W. (The Canadian Field-Naturalist, 2006)
To our knowledge, we present the first published account of a successful attack on a Common Eider (Somateria mollissima) duckling by an Osprey. Ospreys were sighted periodically during 940 hours of Common Eider observations in June-August, 2001 on Grand Manan Island, New Brunswick. One duckling (<1 week old) was observed depredated by an Osprey. Vulnerability of ducklings to predation may promote such opportunistic behaviour. The rarity of observations of such incidents suggests depredation on ducklings by Osprey is uncommon.